Analisis Kontribusi, Efisiensi dan Efektivitas Penerimaan Pajak Daerah terhadap Penerimaan Pendapatan Asli Daerah (PAD) Kabupaten Barito Kuala (Tahun 2014-2019) - Saputro, Setyo Edy; Saleh, Muhammad (PPJP ULM, 2022)
This study aims to determine the level of contribution, efficiency and effectiveness of regional tax revenues in Barito Kuala Regency to Regional Original Income and Regional Taxes in Barito Kuala Regency. regional taxes contained in regional original revenues are charged to local communities by regional governments without obtaining direct reciprocity from the taxes that have been paid. This is a quantitative descriptive study that uses contribution, efficiency and effectiveness analysis using secondary data sourced from the Budget Realization Report obtained from the Regional Financial and Asset Management Agency (BPKAD) and the Regional Tax and Levy Management Agency (BP2RD) of Barito Kuala Regency. The results of this study indicate that in Barito Kuala Regency, the largest contribution level to local taxes and local revenue is BPHTB, followed by Street Lighting Tax. Revenue efficiency can be said to be efficient because local tax levies are below 40%. The overall tax effectiveness is very effective because it exceeds 100%.